Kepemimpinan Hindu Dalam Geguritan Darma Kaya - I Wayan Semita (Jayapangus Press, 2019)
The importance of applying the noble values ​​in the teachings of Hinduism, because to be a strong and disciplined generation is closely related to the souls of a strong leader and understanding of science both spiritual and physical knowledge, natural knowledge and religious knowledge Not only in ancient times ( the kingdom) the problem of leadership arises, in the present century the position of leader is seen as a more competitive arena, so that the process of achieving it seems to escape the theoretical order even to ethical and moral violations. The consequences of this method often produce figures that are not professional. So that its leadership cannot carry out its duties properly, but it actually causes misery for the people it leads. One of the gaguritan literature works that attracts attention is